ANALISIS KESALAHAN PENULISAN汉字 (HANZI) DALAM PEMBELAJARAN BAHASA MANDARIN SISWA KELAS VIII SMP ISLAM ATHIRAH II MAKASSAR - Evie Gita Aryatri; Misnawaty Usman; Burhanuddin Burhanuddin (Universitas Negeri Makassar, 2020)
Abstract. This research aims to classify the types of errors made by the 8th grade students of Athirah Islamic Middle School II Makassar in writing 汉字 (Hànzì) of Mandarin language. The type of this research is descriptive quantitative which collecting the data by doing a writing in汉字 (Hànzì) tests and questionnaires. The analysis method used is the error analysis method by Tarigan (2013). The population of this research is all the students of 8th grade in Athirah Islamic Middle School II Makassar who chose Mandarin as an optional subject totaling 15 of students which is as the total sample. The results of data analysis showed that the writing error of 汉字 (Hànzì) was at the frequency of 96 or 64% and 13 or 13.57% as the highest errors for the character 年 (nián) which means